Sheds Light on the Meaning of Brotherhood through the Samaritan Woman an Integrated Exegetical Approach to John 4:1-42 - Naibaho, Megawati (Forum, 2025)
The story about Jesus meeting with the Samaritan woman was not interesting. This story is not only uninteresting to many people in general but also to the Gospel writers. The researchers is interested in reflecting on the story of the encounter between Jesus and the Samaritan woman. The story of the encounter between Jesus and the Samaritan woman indicates many lessons for building sincere relations with others, especially lessons about respecting, loving, and establishing brotherhood with people who are different from us. The existing differences are not a reason for hostility but rather a beauty and uniqueness in brotherhood. The research uses an integral exegetical approach which is a literature study to explore important messages from the story of Jesus' encounter with the Samaritan woman. This story shows a portrait of the Kingdom of God as proclaimed by Jesus. It is a revealing story with important lessons for us today. Jesus requested that water from Jacob's well be given to the Samaritan woman. The Samaritan woman's willingness to give water to Jesus shows an attitude of sharing with those in need. This story teaches the meaning of life. The implication of this study is an invitation to build true brotherhood